The Results of Test Cases Examining the Effects of Atmospheric Forcing in Limited Area Ice Models - Preller, Ruth; Posey, Pamela G. (1989)
Atmospheric forcing from the Naval Operational Global Atmospheric Prediction System has been to drive the U.S. Navy's operational ice models, the Polar Ice Prediction System and the Regional Polar Ice Prediction System- Barents. Unlike many ocean circulation models which depend mainly on wind forcing, ice models are dependent on winds as well as atmospheric heating/ cooling (fluxes, air temperatures and solar radiation). Comparisons of the ice model results with observations have shown that the model derived fields are highly sensitive to the atmospheric forcing. An excessively warm atmosphere can cause huge ice melting events while an atmosphere which is to cool can cause ice to grow where none has been observed. Wind forcing also plays a major role in the ice model results. Over the short periods of time used in a forecast, winds are dominant in determining ice drift. If the wind is inaccurate, modeled ice drifts are shown to reflect these inaccuracies. The resolution of the atmospheric models are often of the order of hundreds of kilometers, while the ice model's resolution is generally less than 100 km. Mesoscale features are often lost in the coarse resolution of the atmospheric forcing and are therefore missing from the ice model forecasts.